How EF-Tu can contribute to efficient proofreading of aa-tRNA by the ribosome - Jeffrey K. Noel (Nature Portfolio, 2016)
The translation of mRNA by the ribosome is governed by a series of large-scale conformational transitions. Here the authors use MD simulations to demonstrate how the rate of dissociation of elongation factor Tu affects the dynamics of tRNA accommodation and proofreading.